MODELO DE ENSEÑANZA-APRENDIZAJE PARA ADULTOS EN LA ERA DEL CONOCIMIENTO. DISEÑO Y ESTRUCTURA DEL MODELO - Schalk Quintanar, Ana Elena (2005)
This issue assesses the pedagogical process being presented at the international e learning seminar last October at the management faculty of San Marcos University. Fundamentals, actors, structure, and interrelations defining a meaningful, pertaining, relevant learning for development of prospective of training competencies.